Pengaruh Pengalaman Kerja Terhadap Kinerja Pegawai Dinas Pekerjaan Umum Dan Tata Ruang Kabupaten Batang Hari Jambi - Choiri, Miptahul (Magister Ilmu Akuntansi Universitas Jambi, 2025)
This study aims to analyze the effect of work experience on employee performance at the Public Works and Spatial Planning Office (PUTR) of Batang Hari Regency. The research employed a quantitative approach with a survey method, in which the entire population of 89 employees was used as the research sample through a saturated sampling technique. Primary data were collected using questionnaires developed based on indicators of work experience and performance, and subsequently analyzed using simple linear regression with the aid of SPSS software. Theoretically, the implications of this study emphasize the importance of work experience as part of human capital that significantly contributes to performance improvement, while also enriching the literature on human resource management in the public sector. Practically, the findings provide a basis for local governments to design employee development policies based on experience, such as job rotation, involvement in strategic projects, and technology-based training. Thus, this study not only expands scientific knowledge but also offers concrete contributions to improving the effectiveness of employee management and the quality of public services at the regional level.